2019
DOI: 10.1111/jvp.12763
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of levamisole in the red‐eared slider turtles (Trachemys scripta elegans)

Abstract: The pharmacokinetics and bioavailability of levamisole were determined in red‐eared slider turtles after single intravenous (IV), intramuscular (IM), and subcutaneous (SC) administration. Nine turtles received levamisole (10 mg/kg) by each route in a three‐way crossover design with a washout period of 30 days. Blood samples were collected at time 0 (pretreatment), and at 0.25, 0.5, 1, 1.5, 3, 6, 9, 12, 18, 24, 36, and 48 hr after drug administration. Plasma levamisole concentrations were determined by a high‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…For LVM at the same dose and route of administration to red‐eared slider turtles, almost the same values were reported: C max , T max , and t 1/2ʎz values of 10.51 μg/mL, 0.5, and 9.43 h (Corum et al, 2019). Further, Corum et al (2019) also reported a bioavailability of over 100%. Surprisingly, the s.c. bioavailability was higher than 100% for both drugs investigated in the present study.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…For LVM at the same dose and route of administration to red‐eared slider turtles, almost the same values were reported: C max , T max , and t 1/2ʎz values of 10.51 μg/mL, 0.5, and 9.43 h (Corum et al, 2019). Further, Corum et al (2019) also reported a bioavailability of over 100%. Surprisingly, the s.c. bioavailability was higher than 100% for both drugs investigated in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…This could be due to a flip-flop effect (Toutain & Bousquet-mélou, 2004b). For LVM at the same dose and route of administration to red-eared slider turtles, almost the same values were reported: C max , T max , and t 1/2ʎz values of 10.51 μg/mL, 0.5, and 9.43 h (Corum et al, 2019).…”
Section: Ta B L Ementioning
confidence: 53%
See 2 more Smart Citations
“…Another factor that may have led to this difference is the diverse collection schedule up to 12 hr in Zanon et al (2012) study and the diverse pharmacokinetic approach (two‐compartment vs. noncompartmental [present study]). Differently, red‐eared slider turtles after levamisole IM administration at the dose of 10 mg/kg displayed a t 1/2 λz of 7.88 hr (Corum et al, 2019). The difference might be due to the slow drug metabolism, and cardiac output reported in reptiles (Krosniunas & Hicks, 2003; Stamper et al, 2003).…”
Section: Discussionmentioning
confidence: 99%